Breathing Out Completely Before Inhalation: The Most Problematic Step in Application Technique in Patients With Non-Mild Chronic Obstructive Pulmonary Disease - Vytrisalova, Magda; Hendrychova, Tereza; Touskova, Tereza; Zimcikova, Eva; Vlcek, Jiri; Nevoranek, Libor; Svoboda, Michal; Hejduk, Karel; Brat, Kristian; Plutinsky, Marek; Novotna, Barbora; Musilova, Pavlina; et al. (Frontiers in Pharmacology, 2019)
Background Everyday practice adherence to application technique (A-ApplT) of inhaled medication constitutes a major health-care problem in patients with chronic obstructive pulmonary disease (COPD); however, studies evaluating it properly are scarce. The aim of our study was to introduce universal easy-to-use method and assess A-ApplT of chronic medication in moderate to very severe COPD individuals. Methods The Czech Multicentre Research Database (CMRD) of COPD, a large observational prospective study, was used as a source of real clinical data. A-ApplT was evaluated using our Five Steps Assessment. This measure is based on dichotomous evaluation of each of five predefined consecutive steps in application technique and can be used in all settings for all currently available inhalation systems in COPD subjects. Results A total of 546 participants (75.0% men; mean age 66.7 years; mean forced expiratory volume in 1s 44.7%) were available for the analysis. This represents 69.6% of all patients recruited within the CMRD. Less than one third of our participants showed application technique without any erroneous step. The most problematic steps were breathing out completely in one breath immediately before inhalation (step 3), and actual inhalation manoeuvre (step 4). The total number of errors was similar for dry powder inhalers and pressurised metered dose inhalers. Conclusions Our novel instrument, Five Steps Assessment, is comfortable for use in common clinical practice to explore A-ApplT. The A-ApplT in real-life patients with non-mild COPD was absolutely inadequate and should be repeatedly trained with properly (re-)educated medical staff.